2020
DOI: 10.1002/cam4.3306
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes of chemoradiotherapy for unresectable Stage III non‐small cell lung cancer: The SOLUTION study

Abstract: There are limited real‐world data on the treatment practices, outcomes, and safety of chemoradiotherapy (CRT) alone in potential candidates for immune checkpoint inhibitors (ICI) for unresectable non‐small cell lung cancer (NSCLC). In this study, we analyzed the safety and efficacy of CRT in patients who underwent CRT and would satisfy the key eligibility criteria for maintenance therapy with durvalumab (eg, no progression after CRT) in real‐world settings (m‐sub) for unresectable Stage III NSCLC between 1 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
6
19
2
Order By: Relevance
“…The incidence of pneumonitis in this study was similar to that in the Japanese subgroup of the PACIFIC study [2] as well as that in a retrospective Japanese study of chemoradiotherapy for unresectable Stage III NSCLC [3]. Horinouchi et al reported that CRT-related pneumonitis occurred about 10-12 weeks after the completion of CRT in patients with NSCLC [3], consistent with the time of onset of pneumonitis in the present study. Pneumonitis induced with ICI, including durvalumab, occurred at a rate of 1.0% in a phase I/II trial [8].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The incidence of pneumonitis in this study was similar to that in the Japanese subgroup of the PACIFIC study [2] as well as that in a retrospective Japanese study of chemoradiotherapy for unresectable Stage III NSCLC [3]. Horinouchi et al reported that CRT-related pneumonitis occurred about 10-12 weeks after the completion of CRT in patients with NSCLC [3], consistent with the time of onset of pneumonitis in the present study. Pneumonitis induced with ICI, including durvalumab, occurred at a rate of 1.0% in a phase I/II trial [8].…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated that Grade 2 pneumonitis after durvalumab administration following CRT was not associated with a poor prognosis, while pneumonitis before durvalumab administration following CRT was associated with a poor PFS. In our study, the PFS was compatible with that observed in the Japanese subgroup of the PACIFIC trial [3], con rming the reliability of our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, lung cancer is typically classified as small-cell lung cancer (SCLC) and non-SCLC (NSCLC) ( 2 ), with NSCLC being the major type of lung cancer and accounting for 85% of all cases ( 2 ). Despite significant improvements in NSCLC treatment, including surgery ( 4 ), chemotherapy ( 5 , 6 ), radiotherapy ( 7 ), targeted therapy ( 8 10 ) and immunotherapy ( 11 ), the 5-year survival rate of patients with NSCLC is only 15% ( 2 , 12 ). This is due to the absence of early sensitivity and specificity diagnostic biomarkers ( 13 ), drug resistance ( 14 ) and distant metastasis ( 15 ).…”
Section: Introductionmentioning
confidence: 99%